Desarrollo de aplicación web y móvil Android para el control y gestión de ventas aplicando técnicas de data mining en la Embotelladora Agua Fresh. - Silva Zambrano, Kenny Andrés (2023)
It is crucial for a company to control and manage its sales effectively in order to avoid confusion with customers and increase its sales. The increase in sales arises from improved management and the search for information within the company's data. The objective of this research project was to develop a web and Android mobile application for the control and management of sales by applying Data Mining techniques at “Embotelladora Agua Fresh”, a company that is located in La Maná canton. Field research was used as a starting point to obtain initial information about the company and establish the necessary requirements for the development of the web and mobile application. Comparative tables were carried out to select the most appropriate development tools. In order to achieve greater efficiency in development, it was decided to use the agile Scrum methodology and Mobile-D. In addition, the 'Clustering' technique was implemented to apply Data Mining at the company. As a result, a web and mobile application was obtained that allows the control and management of sales, while providing additional data through the grouping of vendors and customers. The company can now manage and control its sales more effectively, making more detailed decisions based on data from the system. Finally, it can discover relevant information about vendors and customers, which contributes to an accurate and efficient decision-making.